Central Banking After Bagehot - Sayers, R. S. (Oxford: Clarendon Press, 1957)
The separate parts follow along so well that one may suspect Sayers of writing a number of them with a sideward glance at the possibility of eventually fitting them together. The result is an indispensable addition to the library of any serious student of central banking
Includes index
Bibliographical footnotes.
osc 22/08/17
Loans
Keywords: Banks and Banking, Central